The power of community as financier : welcome to the world bank of we - Libert, Barry (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from We are smarter than me: How to unleash the power of crowds in your business (9780132244794) by Barry Libert and Jon Spector. How the Internet is revitalizing the tradition of "people-to-people" lending - and how entrepreneurs can take advantage of it!!"--Resource description page.